A EDUCAÇÃO SUPERIOR E O PROLETARIADO: O ACESSO ÀS UNIVERSIDADES PELA CLASSE OPERÁRIA NO ABC PAULISTA - Barbosa, Edson José (2012)
The increasing ease of access to higher education and the need for a broader training led workers with high school and attend the technical academic space that had always held that the right of a small ruling elite leadership trainer. The purpose of this paper is to analyze how the relation of the common laborer with the academic world of universities really influences the working relationships of the Working Class in the factory. A survey in the form of Poll Workers was conducted with the ABC metalworkers to the survey data, taking into account the year to March 1996 with reference to the initial years of the promulgation of LDB 9394/96, in helping to draft the new profile Class of Workers of the ABC region and checking the possible contributions made by the Workers who have completed or are enrolled in college.